2014
DOI: 10.1007/s13402-014-0209-1
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of amino acid metabolism-related genes in gastric and colorectal cancers and their regional heterogeneity - a short report

Abstract: Our data indicate that genes known to be involved in amino acid metabolism recurrently acquire somatic mutations in MSH-H GCs and MSH-H CRCs and that, in addition, mutation ITH does occur in at least some of these tumors. Together, these data suggest that metabolic reprogramming may play a role in the etiology of MSI-H GCs and CRCs. Our data also suggest that ultra-regional mutation analysis is required for a more comprehensive evaluation of the mutation status in these tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The clinical relevance of the molecular detection of DTCs appears to be restricted by both tumor cell heterogeneities [32] and technical limitations. Genomic analyses at a single cell level have shown that DTCs detected with anti-cytokeratin antibodies frequently exhibit heterogeneous tumor-specific aberrations, particularly in patients without overt metastases [33].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical relevance of the molecular detection of DTCs appears to be restricted by both tumor cell heterogeneities [32] and technical limitations. Genomic analyses at a single cell level have shown that DTCs detected with anti-cytokeratin antibodies frequently exhibit heterogeneous tumor-specific aberrations, particularly in patients without overt metastases [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, seven of these 8 mutations (87.5%) were from gastric cancers with MSI, indicating a strong relationship between loss of ACSS2 expression and MSI. A recent study demonstrated that genes known to be involved in amino acid metabolism such as AGXT , ALDH2 , and MTR recurrently acquire inactivating somatic mutations only in MSI‐high gastric and colorectal cancers, indicating that reprogramming of amino acid metabolism due to these mutations may play a role in the etiology of MSI‐high gastric and colorectal cancers . Thus, the role of ACSS 2 in gastric cancer needs to be investigated further in terms of MSI.…”
Section: Discussionmentioning
confidence: 99%
“…(Table)). Similar medium-to-large scale studies have identified mutation in BRD-containing proteins in hepatocellular carcinoma (HCC) 128 , squamous cell lung cancers 129 , lung adenocarcinomas [130][131][132] , small 133 and non-small cell lung cancers 134,135 , adenoid cystic carcinoma 136 , spinal ependymomas 137 , T-cell lymphoma 138 , thymic epithelial tumours 139 , cervical carcinomas 140 , endometrial carcinomas 141 , follicular lymphomas 142 , oesophageal squamous cell carcinomas [143][144][145] , colorectal (CRC) and gastric cancers 146 . However, no systematic studies focusing on the mutation load found on the actual BRD modules themselves exist and as such the contribution of Kac readout to the phenotypes observed remains elusive.…”
Section: Brd-containing Proteins In Cancermentioning
confidence: 99%